A temporary legume sprouts: An alternative for animal feeding - Díaz, María F.; Martín, María A.; Martínez, Madeleidy; Savón, Lourdes; Aguilera, Yolanda; Benítez, Vanesa; Torres, Verena; Coto, G.; González, Acela; Sarmiento, Mariela; Hernández, Yasmila (Cuban Journal of Agricultural Science, 2018)
The use of biological processes, such as germination, that manage to reduce the content of anti-nutritional factors (ANFs) and improve the nutritional value of legume grains from national production, can constitute an option for the production of animal food for small producers, family and backyard agriculture. The results presented in this proposal are related to the obtaining, chemical characterization and nutritional evaluation of temporary legume sprouts as an alternative for animal feeding. For this, it was worked on optimization of the germination process in Vigna unguiculata (vigna) var. INIFAT 94, Canavalia ensiformis (canavalia) var. White, Lablab purpureus (dolicho) var. Rongai, Glicine max (soybean) var. INCASOY 24 and Mucuna pruriens (mucuna) var. Ashen. The transformations that occur during the germination in the physical characteristics, chemical composition, amino acids profile, and (ANFs) content were studied, which constitutes a contribution to scientific knowledge. In addition, the biochemical and physiological effect caused by the intake of germinated and non- germinated grain meals was determined for the first time, in rat as an experimental model and in broilers as a species of economic interest. The obtained results showed that the transformations that occur during germination vary depending on the species and variation of germination used. Germination produced favorable changes in the protein and carbohydrate fraction, increased the total dietary fiber, the proportion of insoluble / soluble dietary fiber and the available starch content, with decrease in the α- galactosides content and increases in total soluble sugars. It proved to be an effective and promising method for the studied legumes when improve the amino acids balance and nutritional quality, reduce anti-nutritional factors, increase bioactive phenolic compounds and antioxidant activity, showing their potential for animal feeding and as a possible ingredient for the formulation of human food with high valueadded. Nutritional studies of germinated grains in birds with inclusion levels in the ration of 20% of vigna, 30% of soybeans and 10% of canavalia and mucuna, showed favorable changes in the digestive physiology and health indicators of the animals, in the specific case of canavalia showed improvement in the immune response. The procedure and experimental sequence used provided methodologies for the selection, collection, characterization and evaluation of sprouts, which can be applied to other species and varieties of legumes with possibilities of use in animal feeding. Key words: legumes, sprouts, chemical characterization, nutritional evaluation